2022
DOI: 10.34172/aim.2022.94
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Prediabetes, and Achievements in Diabetes Control in Iran; The Results of the STEPS of 2016

Abstract: Background: Using the WHO STEPwise approach to NCD risk factor surveillance (STEPS), first round of Iran’s STEPS completed in 2005. It has been repeated six times afterward. Here we report the results of 2016 round on the population characteristics and prevalence of diabetes and prediabetes, along with an assessment of the country-level performance on diabetes care in Iran. Methods: Using a proportional-to-size cluster random sampling method, the STEPS 2016 included 18947 subjects aged≥25 years who matched the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…This study found a higher prevalence of DM among females and a higher prevalence of prediabetes among males. The paradoxical sex difference in the prevalence of DM and prediabetes were consistent with previous STEPS 2016 Survey and other national estimations 9,10,19,20 . It is evident in literature although impaired fasting glucose is more prevalent in males, impaired glucose tolerance is more prevalent in females.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study found a higher prevalence of DM among females and a higher prevalence of prediabetes among males. The paradoxical sex difference in the prevalence of DM and prediabetes were consistent with previous STEPS 2016 Survey and other national estimations 9,10,19,20 . It is evident in literature although impaired fasting glucose is more prevalent in males, impaired glucose tolerance is more prevalent in females.…”
Section: Discussionsupporting
confidence: 91%
“…Previous Iran STEPS Survey 2016 reported the prevalence of DM at 10.6% (10.0-11.1) according to either high FPG or self-report of taking at least one anti-diabetes medication; however, based on other de nitions, the prevalence of DM reached 14.2% (13.6-14.8) 10 . The prevalence of prediabetes in previous STEPS was 16.6% (15.9-17.2) based on 100 ≤ FPG < 126 mg/ dL 10 . In a nationally representative cross-sectional survey of Iranian adults aged 35-70 years as part of the PERSIAN Cohort Study, the sex-and age-standardized prevalence of DM was 15.0% (12.6-17.3), and prediabetes was 25.4% (18.6-32.1) 9 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hypertension was defined as systolic blood pressure ≥ 140 mmHg, diastolic blood pressure ≥ 90 mmHg, or medication use for hypertension [ 27 ]. Diabetes mellitus was defined as an HbA1C ≥ 6.5% (48 mmol/mol), fasting plasma glucose ≥ 126 mg/dl (7.0 mmol/L), or medication use for diabetes [ 28 ]. Stroke was defined as a permanent change in sensory, motor activity, or other underlying conditions related to cerebrovascular disease [ 29 ].…”
Section: Methodsmentioning
confidence: 99%